La estimulación y la inteligencia emocional en los niños de inicial 2 del Centro de Educación Inicial “Alfredo Costales Cevallos” Cantón Riobamba - Huaraca Toaza, Monica Alexandra (2024)
The present research focuses on the stimulation and emotional intelligence in the children of Initial 2 of the "Alfredo Costales Cevallos" Initial Education Center in the Riobamba canton, which is of vital importance to promote adequate emotional control and mental skills from an early age to correct learning and cognitive development. The general objective of the study is to determine how stimulation influences the emotional intelligence of children, improving their emotional expressions in everyday situations. The methodology used is descriptive and explanatory, with a non-experimental design. This study uses a qualitative approach to analyze how emotional and cognitive skills develop and manifest through direct observation in the educational environment. The study population includes children from Initial 2, using direct observation techniques and validated observation sheets to collect data. The results showed that the majority of children are at an intermediate level of stimulation and a medium level of emotional intelligence. A high positive correlation was found between stimulation and emotional intelligence, confirming the hypothesis that stimulation significantly influences the emotional development of children. The conclusions indicate that adequate stimulation contributes directly to the development of emotional intelligence, improving children's ability to interact and understand both their own emotions and those of their peers. The proposed activities provide a playful and safe framework to explore emotions, promoting social and communication skills essential for the comprehensive development of children.